MAGNETIC SUSCEPTIBILITIES AND MAGNETIC MOMENTS OF NITROGEN CONTAINING CHELATE (Proceedings of the YSU B: Chemical and Biological Sciences, 2014)
The magnetic susceptibilities and effective moments of complexes consisting of nitrogen containing ligands and Ni2+, Co2+, Cu2+ ions were studied. It was shown, that complexes listed bellow are paramagnetic and are subjected to the law of Curie–Weiss.
Keywords: magnetic susceptibility, magnetic moment, chelate complex